2021
DOI: 10.1186/s12889-021-11644-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a school-based participatory intervention to improve school environments using the Consolidated Framework for Implementation Research

Abstract: Background Participatory research offers a promising approach to addressing health inequities and improving the social determinants of health for diverse populations of adolescents. However, little research has systematically explored factors influencing the implementation of participatory health interventions targeting health disparities. Objective This study examined the utility of the Consolidated Framework for Implementation Research (CFIR) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…As the administrative leader within schools, executives have the potential to influence implementation of health programs via endorsement, providing oversight and accountability, and/or enacting formal requirements [ 50 ]. In a 2021 evaluation of a school-based participatory health intervention, the level of leadership engagement by school administrators strongly distinguished between high and low implementation schools [ 51 ]. Similarly, an evaluation of a multi-strategy school smoking prevention program found that high- and medium- implementation schools had higher levels of administrative leadership than low implementation schools (77.3 and 83.3% vs 42.9%) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the administrative leader within schools, executives have the potential to influence implementation of health programs via endorsement, providing oversight and accountability, and/or enacting formal requirements [ 50 ]. In a 2021 evaluation of a school-based participatory health intervention, the level of leadership engagement by school administrators strongly distinguished between high and low implementation schools [ 51 ]. Similarly, an evaluation of a multi-strategy school smoking prevention program found that high- and medium- implementation schools had higher levels of administrative leadership than low implementation schools (77.3 and 83.3% vs 42.9%) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study shaped a teacher professional development curriculum to address these gaps and to strengthen student–teacher relationships and school connectedness. 55 We have since integrated this professional development curriculum as one component within a multicomponent pragmatic participatory intervention trial that aims to promote policy and programmatic changes in schools to strengthen school connectedness as a social determinant for students who identify as Black, Indigenous, and People of Color; 56 , 57 final results are forthcoming.…”
Section: Discussionmentioning
confidence: 99%
“…The domains include factors relating to the intervention/innovation (i.e., intervention source, evidence strength and quality, relative advantage, adaptability, trialability, complexity, design quality/packaging, cost), outer setting characteristics (i.e., population needs/resources, cosmopolitanism, peer pressure, external policies/incentives), inner setting characteristics (i.e., structural characteristics, networks/communication, culture, implementation climate, readiness), factors relating to individuals (i.e., knowledge, self‐efficacy, individual stage of change, individual identification with the organization), and process domains (i.e., planning, engaging, executing, reflecting/evaluating). CFIR has been applied to a wide range of implementation studies and interventions within medical settings (Vranceanu et al, 2021), educational and school environments (Koester et al, 2021; Wilhelm et al, 2021), and leadership settings (Shea, 2021). Numerous international studies have also provided evidence for CFIR's use in identifying facilitators and barriers to successful intervention implementation (Busca et al, 2021; Cooper et al, 2021; Vranceanu et al, 2021), while also garnering stakeholder perspective on processes of intervention implementation (AndrĂ© et al, 2021).…”
Section: Introductionmentioning
confidence: 99%